PREVALENCE OF HEPATITIS B ANTIBODIES IN A REGIONAL HEALTH CENTER IN PARANÁ - Oliveira, Thaynara Michelan de; Tiroli, Carla Fernanda; Montanha, Rafaela Marioto; Bolorino, Natacha; Zandonadi, Maithê Gomes Lima; Gonçalves, Laís Cristina; Pieri, Flávia Meneguetti (Cogitare Enfermagem, 2024)
Objective: To estimate the positivity rate of the Hepatitis B Surface Antigen with demographic characteristics and exposure categories among confirmed cases in the municipalities of the 17th Health Region of Paraná, Brazil. Method: This is a descriptive, quantitative cross-sectional study based on notified/confirmed cases in people aged ≥ 1 year and living in the area of the regional health center between 2017 and 2022. The serological marker was used as the outcome variable, and the exposure variables were categorized using absolute and relative frequencies, the Chi-square test, and Fisher's exact test. Results: The variables gender, age group, pregnancy, schooling, and exposure to injecting drugs showed a statistical difference between the groups with a positive rate for the reactive marker. Conclusion: It is important to train health professionals in the use of rapid tests and in filling out the form in full so that they know the epidemiological profile of each region and can draw up specific strategies for prevention, control, and treatment.